MORFOGENESIS DAERAH DANAU KALDERA MANINJAU, SUMATERA BARAT - Santoso Santoso; Ungkap M.Lumbanbatu (Jurnal Geologi dan Sumberdaya Mineral, 2007)
Geomorphologically, the investigated area can be classified into several morphologic origins, i.e: volcanic, fluvio-volcanic, volcanic denudated, denudational, structural-volcanic and fluvial. Moreover, on the basis of the aerial photo interpretation and ground checking, two volcanic cones can be recognized, i.e., old and young Maninjau volcanoes. This assumption supported by the bathymetry map of the Maninjau Lake that shows two points of maximum depth at different locations, -168 m in the north and -169 m in the south sides respectively. These data indicate that the volcano has two different eruption centres.Â Keywords: geomorphology, fluvio-volcanic, denudational, structural